Mitochondrial quality control in lung diseases: current research and future directions - Liu, Jiliu; Wang, Junyi; Xiong, Anying; Zhang, Lei; Zhang, Yi; Liu, Yao; Xiong, Ying; Li, Guoping; He, Xiang (Frontiers in Physiology, 2023)
Lung diseases are a major global health problem, affecting millions of people worldwide. Recent research has highlighted the critical role that mitochondrial quality control plays in respiratory-related diseases, including chronic obstructive pulmonary disease (COPD), lung cancer, and idiopathic pulmonary fibrosis (IPF). In this review, we summarize recent findings on the involvement of mitochondrial quality control in these diseases and discuss potential therapeutic strategies.Mitochondria are essential organelles for energy production and other cellular processes, and their dysfunction is associated with various diseases. The quality control of mitochondria involves a complex system of pathways, including mitophagy, mitochondrial biogenesis, fusion/fission dynamics, and regulation of gene expression.In COPD and lung cancer, mitochondrial quality control is often involved in disease development by influencing oxidative stress and apoptosis. In IPF, it appears to be involved in the disease process by participating in the cellular senescence process.Mitochondrial quality control is a promising target for therapeutic interventions in lung diseases. However, there are conflicting reports on different pathological processes, such as the role of mitochondrial autophagy in lung cancer, which pose difficulties in the study of targeted mitochondrial quality control drugs. Additionally, there seems to be a delicate balance between the mitochondrial quality control processes in the physiological state. Emerging evidence suggests that molecules such as PTEN-induced putative kinase 1 (PINK1), parkin RBR E3 ubiquitin protein ligase (PRKN), dynamin-related protein 1 (DRP1), and peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC1-α), as well as the signaling pathways they affect, play an important role in respiratory-related diseases. Targeting these molecules and pathways could contribute to the development of effective treatments for lung diseases. In conclusion, the involvement of mitochondrial quality control in lung diseases presents a promising new avenue for disease treatment. Further research is needed to better understand the complex mechanisms involved in the pathogenesis of respiratory diseases and to develop targeted therapies that could improve clinical outcomes.